BADAN NARKOTIKA NASIONAL (BNN) KOTA PAYAKUMBUH DAN PENANGGULANGAN PENYALAHGUNAAN NARKOBA PADA REMAJA - Siti Arifah Asri Amir; Farid Putera (Ensiklopedia of Journal, 2020)
This research is motivated by the reality on the ground that drug abuse against adolescents in Indonesia, especially Payakumbuh City is increasingly worrying with large economic and social impacts. Seeing the reality of drug abuse against teenagers who still exist, it is necessary to see how the implementation of the functions and roles of institutions that deal with drug problems, namely the Payakumbuh National Narcotics Agency and the obstacles faced in tackling drug abuse. This type of research is qualitative using descriptive method. Descriptive qualitative research is research that intends to understand the phenomenon of what is experienced by the research subject The findings of this study are A. Implementation of the Functions and Roles of the National Narcotics Agency in Payakumbuh City in Overcoming Drug Abuse in Adolescents in Payakumbuh City. 1. The P2M section carries out socialization and counseling to SMP, SMA students in Payakumbuh City and empowers them by forming anti-drug volunteers. 2. The Rehabilitation Section opens rehabilitation services every working day at the Payakumbuh BNNK Office and socializes that drug abusers who report are not criminalized. 3. The Eradication Section has not been able to carry out investigations due to limited personnel. B. Obstacles faced by BNNK Payakumbuh in carrying out its functions and roles. 1. Payakumbuh community awareness and concern for the dangers and abuse of drugs needs to be increased by outreach to all levels of society. 2. The limited number of Payakumbuh BNNK personnel makes performance not optimal. Currently the number of personnel is 28 people, while the ideal is 60 people. In an effort to tackle drugs against teenagers, BNNK Payakumbuh will continue to strive in carrying out its duties based on existing regulations, and will continue to evaluate drug control strategies to create a physically and mentally healthy Payakumbuh community.Keywords: Function, National Narcotics Agency, Drugs, Youth.